Enlivening Cultural Environments through Sharing and Gotong Royong (Mutual Cooperation) - Diane Butler (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
The development of best practices and cooperative approaches that ensure the active participation of local communities in identifying and safeguarding tangible and intangible cultural heritage for the long-term has become a major aim of cultural policies in recent decades. This paper proposes that the value of sharing and custom termed gotong royong (mutual cooperation), still an intrinsic part of daily life in most villages in Indonesia and in several Southeast Asian nations, is a means by which traditional cultural environments can be enlivened in the present. In particular, art practices show the contemporary value and efficacy of traditional forms of social cooperation and can foreground the continuing role of local ethnic communities, as the caretakers of the various elements of tangible and intangible cultural heritage present in their territory. To illustrate why and how, I draw on examples of art practice from public participatory intercultural events held in Bali and Java, Indonesia as well as in other countries.